A Kinetic Study of the Effects of Light on Circadian Rhythmicity of the frq Promoter of Neurospora crassa. (February 2014) - Gooch, Van D.; Johnson, Alicia E.; Bourne, Brian J.; Nix, Bradley T.; Maas, Jonna A.; Fox, Julie A.; Loros, Jennifer J.; Larrondo, Luis F.; Dunlap, Jay C.
The role of the frq gene in the Neurospora crassa circadian rhythm has been widely studied, but technical limitations have hindered a thorough analysis of frq circadian expression waveform. Through our experiments, we have shown an improved precision in defining Neurospora's circadian rhythm kinetics using a codon optimized firefly luciferase gene reporter linked to a frq promoter. In vivo examination of this real-time reporter has allowed for a better understanding of the relationship of the light responsive elements of the frq promoter to its circadian feedback components. We provide a detailed phase response curve showing the phase shifts induced by a light pulse applied at different points of the circadian cycle. Using the frq-luc reporter, we have found that a 12-h light:12-h dark cycle (12L:12D) results in a luciferase expression waveform that is more complex and higher in amplitude than that seen in free-running conditions of constant darkness (DD). When using a lighting regime more consistent with solar timing, rather than a square wave pattern, one observes a circadian waveform that is smoother, lower in amplitude, and different in phasing. Using dim light in place of darkness in these experiments also affects the resulting waveform and phasing. Our experiments illustrate Neurospora's circadian kinetics in greater detail than previous methods, providing further insight into the complex underlying biochemical, genetic, and physiological mechanisms underpinning the circadian oscillator.